EVALUATION OF INTEGRATED DEVELOPMENT OF THE ENTERPRISE - Boichenko Kateryna Stepanivna; Klymenko Svitlana Mihailivna; Terentieva Olena Volodimirivna; Kuznetsova Nataliya Bogdanivna (Scientific Journal of Pedagogy and Economics, 2020)
The purpose of this article constitutes the formulation of a methodological approach to assessing and increasing the level of the integrated development effectiveness of Ukrainian light industry enterprises, taking into consideration the modularized diagnostics of their activity. Methods. The methodological toolkit for the effectiveness evaluation of integrated development of the enterprise is based on an integral indicator subject to the economic, organizational, informational and innovative integration modules. To undertake the study, 30 Ukrainian light industry enterprises were selected. The development diagnostics was carried out for each of them according to the key performance indicators and an integral indicator of the business development level was determined. Results. Seven groups of the enterprises were formed, and resulting from their integrated development, an increase in its level was received at all companies. The highest development growth was recorded at such companies as Orion, Kalyna, Lybid, Shovkova nytka and Lileya. These companies can significantly improve performance, through their development integration. A feature of the proposed orbital-based methodology is the stimulation of the development level increasing of both an individual enterprise and the industry as a whole, since less developed companies do not reduce the development level of others, but reach a higher level due to integration with the similar economic entities. Conclusions. The proposed orbital-based methodology implies the stimulation of the development level increasing of both an individual enterprise and the industry as a whole. It allows comprehensively to assess the enterprise`s performance by individual modules; to identify and compare the alternative development options; to determine deviations in the process of its functioning and to make adjustments to activities on time.